Update on the Diagnosis of Traveler’s Diarrhea: Current Strategies and Emerging Trends - Kennedy Winata; Kartika Cahyaningrum; Dayana Puspawarna; Ngakan Satria Wibawa; Agung Kesuma Putra; Bagas Aditya Kurnia Pratama; Eva Santhy; Adi Arya; Miracle Lie; Herliana Yuliartha; Arnelia Tasau; Arya Giri Prebawa; Saraswati Laksmi Dewi (Publication Department, Universitas Warmadewa, 2024)
Traveler’s diarrhea (TD) remains a prevalent condition affecting individuals traveling to regions with varying sanitation standards. The diagnosis of TD has evolved with advancements in diagnostic tools and a better understanding of its etiology. Traditionally diagnosed based on clinical presentation and exposure history, current approaches increasingly incorporate molecular techniques to identify causative pathogens more accurately. Recent updates highlight the integration of polymerase chain reaction (PCR) and other molecular diagnostic methods that offer rapid, sensitive, and specific detection of bacterial, viral, and parasitic pathogens. These advances enable differentiation between infectious and non-infectious causes of diarrhea, which is crucial for effective management and treatment. Additionally, the role of stool cultures, although less commonly used in rapid diagnostics, remains important for comprehensive pathogen identification. Emerging research emphasizes the need for a tailored diagnostic approach considering geographic region, patient history, and symptom profile. The use of multiplex assays and metagenomic sequencing is showing promise in identifying a broad spectrum of pathogens and understanding the complex microbiological landscape of TD. This update underscores the importance of adopting a multifaceted diagnostic strategy to improve the accuracy of TD diagnosis, thereby enhancing patient care and contributing to the development of targeted treatment and preventive measures.